(untitled) (Bangladesh Journal of Zoology, 2016)
A total of 115 Clarias batrachus were investigated for parasitic infestation. Out of 1504 parasites recovered from Clarias batrachus, 761 (50.59%) were cestodes, 34(2.26%) trematodes, 58(3.85%) nematodes and 12(0.79%) crustaceans ectoparasite. Cestodes showed the highest prevalence (66.09%) and the collected parasites were Bovienia serialis, Caryophyllaeus laticeps, Balanotaenia bancroftii, Djombangia penetrans, Orientocreadium batrachoides, Orientocreadium clariae, Procamallanus slomei, Spirocamallanus olsenia and ectoparasite Lernaea cyprinacea. Among the 9 species of parasites, P. slomei (28.69%) showed the highest prevalence. The moderate prevalence showed by Bovienia serialis and S. olsenia (21.74), lowest by O. batrachoides (10.43%) and Lernaea cyprinacea (10.43). The overall prevalence and mean intensity of parasite infection were 82.61% and 15.83 respectively. The highest parasitic infestation was found (88.43%) in intestine. Cestodes B. serialis, B. bancroftii and D. penetrans were recovered from stomach and intestine. P. slomei were collected from three regions viz. oesophagus, stomach and intestine, while Lernaea cyprinacea from gill. Seasonally the highest prevalence (90%) and mean intensity (24.27%) was recorded during summer. Bangladesh J. Zool. 43(2): 269-277, 2015